Addressing the Housing Crisis: Insights from a Study on University Students in Turkey - Sarıipek, Doğa Başar; Peker, Zahide; Cerev, Gökçe (Social Welfare: Interdisciplinary Approach, 2024)
Housing stands as a fundamental human right, acknowledged by numerous international bodies and statutes. Despite this recognition, only a handful of nations ensure adequate housing for their populace. This research endeavors to forge a connection between housing rights and social policy through a comprehensive literature review. Drawing from data provided by the Turkish Statistical Institute and the Ministry of Youth and Sports, the study addresses the escalating housing concerns among university students in Turkey. With an increasing student population and insufficient accommodation facilities, the issue has reached a critical juncture. Most students are compelled to reside in state dormitories, which lack the capacity to meet demand. Moreover, economic hardships and a dearth of financial aid exacerbate the housing crisis. The findings underscore the urgent need for the development of policies and solutions tailored to address the housing predicament faced by university students in Turkey.